2016
DOI: 10.1186/s12879-016-1584-1
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Hepatitis C prevalence estimates in Sub-Saharan Africa: 2000–2013

Abstract: BackgroundHepatitis C (HCV) is a deleterious virus that can be cured with new, highly effective anti-viral treatments, yet more than 185 million individuals worldwide remain HCV positive (with the vast majority un-diagnosed or untreated). Of importance, HCV is a leading cause of chronic liver disease and liver cancer, especially in Sub-Saharan Africa (SSA) where the prevalence remains high but uncertain due to little population-based evidence of the epidemic. We aimed to synthesize available data to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 14 publications
3
25
5
1
Order By: Relevance
“…The overall sero-prevalence of anti-HCV in the study area was 1.9%. The overall sero-prevalence of anti-HCV recorded in our study area was less than that from the pooled national prevalence of 3.1% [22] and 3.0% reported in Sub-Saharan Africa [30]. However, it is still greater than the 1.0% prevalence reported from Gojjam, Ethiopia [29]; 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan [31] among the general populations.…”
Section: Discussioncontrasting
confidence: 64%
“…The overall sero-prevalence of anti-HCV in the study area was 1.9%. The overall sero-prevalence of anti-HCV recorded in our study area was less than that from the pooled national prevalence of 3.1% [22] and 3.0% reported in Sub-Saharan Africa [30]. However, it is still greater than the 1.0% prevalence reported from Gojjam, Ethiopia [29]; 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan [31] among the general populations.…”
Section: Discussioncontrasting
confidence: 64%
“…A prevalence of 4.4% was reported from a neighbouring country, Ghana and 1.8% for Libya and 0.11% for California, USA [20,35,36]. A prevalence rate of 4.14% has been reported for Western Africa where Nigeria falls [34]. Trends of infection among the blood donors for HCV and HIV infection showed a similar pattern of moderate fluctuation.…”
Section: Discussionmentioning
confidence: 54%
“…Studies on HCV prevalence in Sub Saharan African showed that blood donors consistently had lower prevalence (1.9 %) than the general population prevalence [34]. A prevalence of 0.8 to 6.0% has been reported among blood donors in Nigeria [4,5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Across Sub‐Saharan Africa, prevalence of malaria during pregnancy (peripheral parasitemia) ranges between 29.5% (in Eastern and Southern Africa) and 35.1% (in Western and Central Africa) . Estimates for hepatitis are high, with a median of 4.3% of pregnancies diagnosed with seroprevalence of hepatitis B serum antigen (HBsAg), and between 2.5% and 3.0% of pregnant women in Africa infected with hepatitis C (Table ).…”
Section: Resultsmentioning
confidence: 99%